2004
DOI: 10.4049/jimmunol.172.9.5664
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Experimental Ulcerative Colitis Is Mediated by Eosinophil Peroxidase

Abstract: The precise role that individual inflammatory cells and mediators play in the development of gastrointestinal (GI) dysfunction and extraintestinal clinical manifestations of ulcerative colitis (UC) is unknown. In this study, we have used a mouse model of UC to establish a central role for eotaxin and, in turn, eosinophils in the development of the immunopathogenesis of this disease. In this model the administration of dextran sodium sulfate (DSS) induces a prominent colonic eosinophilic inflammation and GI dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
149
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 59 publications
10
149
0
2
Order By: Relevance
“…Furthermore, as indicated above, granule proteins such as eosinophil cationic protein, Epx, and major basic protein released by activated eosinophils during inflammation can contribute to tissue damage (alter barrier function) and dysfunction (diarrhea with bleeding) 9, 10, 11, 12. Deficiency of eotaxin‐1, the eosinophil‐specific chemokine, or blockade of its receptor (CCR3) resulting in depletion of eosinophils has been shown to attenuate inflammation in experimental models of IBD,9, 28 thus supporting the overall importance of eosinophil involvement in EGID.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as indicated above, granule proteins such as eosinophil cationic protein, Epx, and major basic protein released by activated eosinophils during inflammation can contribute to tissue damage (alter barrier function) and dysfunction (diarrhea with bleeding) 9, 10, 11, 12. Deficiency of eotaxin‐1, the eosinophil‐specific chemokine, or blockade of its receptor (CCR3) resulting in depletion of eosinophils has been shown to attenuate inflammation in experimental models of IBD,9, 28 thus supporting the overall importance of eosinophil involvement in EGID.…”
Section: Discussionmentioning
confidence: 99%
“…14,52 Eosinophil accumulation in the mucosa is a common feature observed during DSS-induced colitis in mice. 16,17 We and others have previously shown that TLR2 signaling in response to the commensal microflora is important in limiting mucosal injury during DSS colitis. 25,26 TLR2-deficient animals have been shown to have a more severe disease development, with an extended time course and slower recovery after cessation of DSS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In untreated mice, there were no significant differences between TLR2 Ϫ/Ϫ and control mice in the levels of IL-5 or CCL11 in the cecum or the mid-colon (Figure 2). After DSS treatment, cecal and colonic CCL11 levels significantly increased in both groups of mice; however.…”
Section: Absence Of Cecal and Mid-colonic Eosinophils In Tlr2 ϫ/ϫ Micmentioning
confidence: 95%
See 2 more Smart Citations